Extracción por prensado en frio y valoración de las características fisicoquímicas y sensoriales del aceite de dos variedades de aguacate” (Persea Americana) - Cuchipe Chacha, Cristian Israel (2023)
The present research work is given with the purpose of extracting oil by the cold pressing method, with different varieties of avocado, in order to quantify the lipid content of the best treatment, through a physical, chemical, sensory and statistical analysis that define the quality of the oil for food use and comply with current regulations, for this the Hass and Fuerte (Persea americana) varieties that are cultivated in the Sigchos canton were studied, for this the extraction method by cold pressing was used, having as objective, to analyze the physicochemical characteristics (moisture, acidity, density, impurities), sensory (color, taste, smell, acceptability) and the best treatment (impurity index, density, iodine index, peroxide index, refractive index) , microbiological (Molds, yeasts and mesophilic aerobics), calculate the cost and performance. The study factors were A: Material and genetics (Hass and Fuerte), Factor B: Dehydration temperature and time, (65ºC x 10h; 80ºC x 8h) and Factor C: Pressure and extraction time (200 bar. x 5 min. .;250 bar x 3 min). For the elaboration of this project, an experimental design was applied under an AxBxC factorial arrangement of a completely randomized block design with a total of 16 treatments and 2 repetitions.